Immersion vaccination of Atlantic salmon (Salmo salar) against Yersinia ruckeri - Nguyen, TD; Andrew Bridle; Barbara Nowak (2015)
Yersinia ruckeri is a pathogen which causes yersiniosis and significant losses in farmed Atlantic salmon ( Salmo salar ) in the Southern Hemisphere. Currently, Yersinivac-B, a commercial bacterin-based vaccine manufactured by MSD Animal Health and prepared from formalin killed whole-cells, is used for immersion vaccination against Y. ruckeri for most Tasmanian Atlantic salmon. Until recently, these fish were vaccinated once by bath immersion at 5g. However, half a million vaccinated juvenile Atlantic salmon died of yersiniosis in a single Tasmanian hatchery in 2007. In this PhD study, we evaluated different inactivation methods of Y. ruckeri on the efficacy of single dip vaccines including formalin inactivation, ammonium sulphate inactivation, and pH-lysed then formalin inactivation. Additionally, hyperosmotic infiltration was combined with an ammonium sulphate inactivated bacterin in immersion vaccination to assess the protection of these vaccines. The relative percent survival (RPS) afforded was 93.4% for the fish vaccinated with ammonium sulphate inactivated vaccine, 85.4% for fish vaccinated with formalin inactivated vaccine and 81.3% for fish vaccinated with pH-lysed then formalin inactivated vaccine. The results of this study have shown that ammonium sulphate can be used to inactivate Y. ruckeri and can replace formalin inactivation.